2021
DOI: 10.3233/jpd-202285
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Subcutaneous Levodopa Delivery for Parkinson’s Disease: A Randomized Study

Abstract: Background: ND0612 is a continuous, subcutaneous levodopa/carbidopa delivery system in development for patients with Parkinson’s disease (PD) experiencing motor fluctuations Objective: Evaluate the efficacy and safety of two ND0612 dosing regimens in patients with PD. Methods: This was a 28-day open-label study (NCT02577523) in PD patients with ≥2.5 hours/day of OFF time despite optimized treatment. Patients were randomized to treatment with either a 24-hour infusion (levodopa/carbidopa dose of 720/90 mg) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Despite the higher levels of levodopa achieved in the ND0612 treatment group, it was not associated with an increase in peak-dose dyskinesia, as often seen with oral levodopa administration [26]; no dyskinesias were reported as TEAE and mean UPDRS Part IVa scores remained relatively unchanged in both groups. These data support the findings of another Phase 2 study which evaluated higher levodopa/carbidopa dosing with ND0612 (levodopa/carbidopa dose of 720/90 mg) and found that 24 h infusion with ND0612 reduced OFF time by an adjusted mean of 2.8 h (p = 0.004 vs. baseline) [27].…”
Section: Discussionsupporting
confidence: 86%
“…Despite the higher levels of levodopa achieved in the ND0612 treatment group, it was not associated with an increase in peak-dose dyskinesia, as often seen with oral levodopa administration [26]; no dyskinesias were reported as TEAE and mean UPDRS Part IVa scores remained relatively unchanged in both groups. These data support the findings of another Phase 2 study which evaluated higher levodopa/carbidopa dosing with ND0612 (levodopa/carbidopa dose of 720/90 mg) and found that 24 h infusion with ND0612 reduced OFF time by an adjusted mean of 2.8 h (p = 0.004 vs. baseline) [27].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that ND0612 provides stable plasma levodopa concentrations, 1 significantly reduces daily OFF time, 1,2 and increases ON time without significant dyskinesia. 2 The primary aim of this study was to assess the long-term safety and tolerability of ND0612 over 12 months of treatment, with a particular focus on infusion site reactions (ISRs) that are often associated with SC drug administration.…”
Section: Nd0612 (Neuroderm Ltd Rehovot Israelmentioning
confidence: 97%
“…Conclusions: Subcutaneous levodopa/carbidopa continuous infusion with ND0612 is generally safe, with typical infusion site reactions for SC delivery as the main adverse event. 1 significantly reduces daily OFF time, 1,2 and increases ON time without significant dyskinesia. 2 The primary aim of this study was to assess the long-term safety and tolerability of ND0612 over - --------------------------------------------------------12 months of treatment, with a particular focus on infusion site reactions (ISRs) that are often associated with SC drug administration.…”
mentioning
confidence: 96%
“…Alternatively, Duodopa is a continuously infused intrajejunal gel of carbidopa/levodopa [59]. Additionally, subcutaneous infusion of carbidopa/levodopa is under evaluation [60,61]. The major side-effects of carbidopa/levodopa are the development over time of dyskinesia and fluctuating 'off-on' periods of effectiveness [5].…”
Section: Therapy Options For Treating Motor Symptoms Of Pdmentioning
confidence: 99%